High angular resolution observations of binary protostars - Chen, Xuepeng (2008)
In this thesis I present a systematic effort to reveal the physical processes that lead to the formation of binary stars. We have observed, at high angular resolution, thirteen isolated low-mass protostellar cores, using the Owens Valley Radio Observatory millimeter array, the Australia Telescope Compact Array, and the IRAM Plateau de Bure Interferometer array. The observations were mainly carried out in the N2H+(1-0) line and at 3mm dust continuum. The results were complemented by infrared data from the Spitzer Space Telescope and the ESO Very Large Telescope. We find that binarity/multiplicity is frequent in the protostellar phase, though it is too early to derive a separation distribution. The circumstellar mass ratio distribution of binary protostars appears to be flat like that of more evolved long-period main-sequence binary stars, and more than 75% of protobinary systems have circumstellar mass ratios below 0.5. The specific angular momenta of protostellar cores are intermediate between those of prestellar cores and the orbital angular momenta of wide pre-main sequence binary systems. There appears to be no significant decrease of angular momentum between the onset of the protostellar collapse and the emergence of a binary star, which suggests that most of the angular momentum contained in the collapse region is transformed into orbital angular momentum of the resulting stellar binary system. We find that during core fragmentation the angular momentum is not evenly, in value and direction, divided between sub-cores. Furthermore, most cores with binary protostars have ratios of rotational to potential gravitational energy of beta_rot > 1%. This is consistent with theoretical simulations and suggests that the initial amount of rotational energy in a molecular cloud core is playing an important role in the protostellar fragmentation process.